Ontological security and collective identity through the prism of strategic culture on the example of Kosovo and Metohija - Proroković, Dušan; Stojanović, Bogdan (Sociološki pregled, 2024)
The paper theoretically investigates the phenomena of ontological security and collective identity through the prism of strategic culture, with an empirical elaboration of the case study of Kosovo and Metohija. The authors supplement the realistic understanding of security with a social-constructivist perspective, emphasizing the influence of values, ideas, perceptions and culture in general in the shaping of collective identity, which is closely related to the subjective sense of security. The main hypothesis is that the solidity of the collective identity survives regardless of external pressures and reshaping tendencies because its survival is perceived as an inseparable essence of ontological security. The authors conclude that the strength of collective identity in certain situations overcomes the problems of collapsed institutions and the absence of actors who advocate the basic values of that identity. Kosovo and Metohija is more than a material part of the territory, strongly building the foundations of collective identity. An individual who feels a sense of belonging to such a collective identity will almost instinctively reject any solution which affects that identity, so he will perceive an attack on those values, no matter how intense, as a feeling of personal insecurity.
Keywords: ontological security; collective identity; strategic culture; Kosovo and Metohija; Serbia; values; society